1. Remove parentheses
-3x^2 + x^4 + x + 2x^4 - 7 + 4x
2. Collect like terms
-3x^2 + (x^4 + 2x^4) + (x + 4x) - 7
3. Simplify
-3x^2 + 3x^4 + 5x - 7
Answer:
x = 36
y = 37.95
Step-by-step explanation:
By geometric mean property:
By Pythagoras Theorem:
![{y}^{2} = {12}^{2} + {x}^{2} \\ \\ {y}^{2} = {12}^{2} + {36}^{2} \\ \\ {y}^{2} = 144 + 1296 \\ \\ {y}^{2} = 1440 \\ \\ y = \sqrt{1440} \\ \\ y = 37.95](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20%3D%20%20%7B12%7D%5E%7B2%7D%20%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%5C%5C%20%20%5C%5C%20%20%7By%7D%5E%7B2%7D%20%20%3D%20%20%7B12%7D%5E%7B2%7D%20%20%2B%20%20%7B36%7D%5E%7B2%7D%20%20%5C%5C%20%20%5C%5C%20%20%7By%7D%5E%7B2%7D%20%20%3D%20144%20%2B%201296%20%5C%5C%20%20%5C%5C%20%20%7By%7D%5E%7B2%7D%20%20%3D%201440%20%5C%5C%20%20%5C%5C%20y%20%3D%20%20%5Csqrt%7B1440%7D%20%20%5C%5C%20%20%5C%5C%20%20y%20%3D%2037.95)
Answer:
![y = \frac{29}{5} x \\ \frac{y}{x} = \frac{29}{5}](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B29%7D%7B5%7D%20x%20%5C%5C%20%20%5Cfrac%7By%7D%7Bx%7D%20%20%3D%20%20%5Cfrac%7B29%7D%7B5%7D%20)
<h3>The rate of change is <u>29/5</u>.</h3>
Answer:
(b – 8)(b + 4)
Step-by-step explanation:
The signs of the binomial constants must be different in order for their product to be -32.
The one with the larger magnitude must be negative in order for their sum to be -4. The only viable choice is (b -8)(b +4).